(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Face-the structure of the wound surface in patients with phlegmon of the jaw and neck. The etiological cause of the disease can be hemolytic streptococci, various staphylococci, mixed flora and anaerobic bacteria.In order to avoid other complications in the phlegmon of the face and neck, urgent surgical intervention is carried out: in this case, a wide opening, drainage of cell cavities, adequate antibacterial therapy is carried out.Ludwig angina is a life-threatening condition of purulent inflammatory nature, which is accompanied by diffuse cellulite of the soft tissues of the muscle floor of the oral cavity and neck. The German physician Wilhelm comes from the name Friedrich von Ludwig, which he first described in 1836. It includes three sections of the muscular floor of the oral cavity: the sub-tongue, the submental, and the submandibular. Early detection and treatment, including airway protection, surgery, wound drainage, and adequate antibiotic therapy, are essential.